On Approximation and Generalized Type of Analytic Functions of Several Complex Variables (Analysis in Theory and Applications, 2011)
In the present paper, we study the polynomial approximation of analytic functions of several complex variables. The characterizations of generalized type of analytic functions of several complex variables have been obtained in terms of approximation and interpolation errors.
Keywords: analytic function; Siciak extremal function; generalized type; approximation errors; interpolation errors.